Transformation of Korean politics and administration : a 30 year retrospective - Im, To-bin (Public policy and governance., 2022)
Transformation of Korean Politics and Administration: A 30 Year Retrospectiveretraces critical turning points in Korean history as seen from the historical path dependence theory to help explain the significant changes that have occurred in the major pillars of the Korean politics and administration.